PRKAR1A deficiency impedes hypertrophy and reduces heart size. Issue 6 (25th March 2020) - Liu, Yuening; Xia, Peng; Chen, Jingrui; Bandettini, W. Patricia; Kirschner, Lawrence S.; Stratakis, Constantine A.; Cheng, Zhaokang
Abstract: Protein kinase A (PKA) activity is pivotal for proper functioning of the human heart, and its dysregulation has been implicated in a variety of cardiac pathologies. PKA regulatory subunit 1α (R1α, encoded by the PRKAR1A gene) is highly expressed in the heart, and controls PKA kinase activity by sequestering PKA catalytic subunits. Patients with PRKAR1A mutations are often diagnosed with Carney complex (CNC) in early adulthood, and may die later in life from cardiac complications such as heart failure. However, it remains unknown whether PRKAR1A deficiency interferes with normal heart development. Here, we showed that left ventricular mass was reduced in young CNC patients with PRKAR1A mutations or deletions. Cardiac‐specific heterozygous ablation of PRKAR1A in mice increased cardiac PKA activity, and reduced heart weight and cardiomyocyte size without altering contractile function at 3 months of age. Silencing of PRKAR1A, or stimulation with the PKA activator forskolin completely abolished α1‐adrenergic receptor‐mediated cardiomyocyte hypertrophy. Mechanistically, depletion of PRKAR1A provoked PKA‐dependent inactivating phosphorylation of Drp1 at S637, leading to impaired mitochondrial fission. Pharmacologic inhibition of Drp1 with Mdivi 1 diminished hypertrophic growth of cardiomyocytes. In conclusion, PRKAR1A deficiency suppresses cardiomyocyte hypertrophy and impedes heart growth, likely through inhibiting Drp1‐mediated mitochondrial fission. These findings provide a potential novel mechanism for the cardiac manifestations associated with CNC. Abstract : PRKAR1A mutations in humans are known to cause Carney complex, an autosomal dominant genetic disease often associated with premature death. Here, we report that PRKAR1A deficiency suppresses cardiomyocyte hypertrophy and reduces heart size, likely through PKA‐dependent inhibition of Drp1‐mediated mitochondrial fission.